THE EFFECT OF ACCOUNTING CONSERVATISM ON THE PERSISTENCE OF EARNINGS OF THE BANKS LISTED ON THE IRAQ STOCK EXCHANGE - Basim Mohammed Merhej (Journal of Economic and Economic Policy, 2026)
Objective: This study examines whether accounting conservatism is associated with improved earnings persistence of commercial banks listed in the Iraq Stock Exchange (ISX), and whether this association is conditional on (i) the level of corporate governance and (ii) report reforms aligned with IFRS. Method: Based on a balance sheet of publicly disclosed financial statements and reports concerning the governance of financial statements of banks (1987 or later) (2020-2024, Source: Bank for International Settlements). conditional conservatism (ULI). proxied using the accrual-cash flow asymmetric loss recognition framework of Ball and Shivakumar. See earnings persistence using the autoregressive model in which current earnings depend on lagged earnings. Results: The results show evidence of conditional conservatism that is statistically significant with the interaction between operating cash flows and an indicator for the presence of negative cash flows having a positive and significant effect, consistent with loss recognition being more timely when compared to gain recognition. Earnings also have moderate-to-high persistence (positive and significant lagged earnings coefficient less than unity), so that the current earnings have some meaningful information about their future earnings, but are not perfectly permanent. Further analyses indicate that corporate governance reinforces the conservatism-persistence relationship: the conservatism x governance interaction is positive and significant, which is suggestive of stronger monitoring and oversight increasing the degree to which conservative reporting is followed by more sustainable earnings. Finally, IFRS-consistent reform periods are linked to a stronger relationship between conservatism and persistence, as we demonstrate by the presence of a positive and significant effect of the interaction between conservatism and IFRS. Novelty: Collectively, the findings suggest that, in an institutionally changing market like Iraq, conservatism can enhance earnings sustainability, particularly when it is combined with better governance and more sensible reporting regimes.